Integrated Islamic Education: An Analytcal Study on The Concept and Practice of Gontor System in East Java Indonesia - Imam Bahroni (Universitas Darussalam Gontor, 2010)
The current issue on international education, especially in relation with muslim community, like in Malaysia and Indonesia is morality. The impact and influence of secular civilization upon muslim society can not be denied. The problem of morality is not only an individual but rather touches the level of all social community of muslim ummah all over the world. Consequently every one now needs an education which can fortify the nation from this moral malady. To overcome this problem according to the researcher needs strategy, planning and strong system, such as boarding school based education. Based on above introduction, the researcher wishes to study in this simple research on Gontor system of integrated Islamic education. To reach valid result of study, the researcher wish to use interview, observation and documentary method for the data collection. Meanwhile, for the data analysis, the researcher uses data reduction, display and verification of Miles and Huberman method. The points above, ensures the writer to further explore the data of Gontor system, so then the object of the research could be approved scientifically for the purpose of muslim community all over the world.